2022
DOI: 10.3390/ma15041431
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Dentin Graft after Impacted Mandibular Third Molar Extraction to Prevent Periodontal Pocket Formation—A Split-Mouth Pilot Study

Abstract: This preliminary study aims to evaluate the efficacy of an autologous dentin graft in preventing periodontal defects after impacted or semi-impacted lower third molars’ (M3) surgical extraction. For this purpose, radiographic and periodontal evaluation of post-extractive sockets were performed. Ten patients were enrolled in the study: twenty M3 extraction sockets were treated with a split-mouth modality. After tooth extraction, the experimental sites were filled with autologous dentin graft obtained by the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 42 publications
2
14
0
4
Order By: Relevance
“…Nghiên cứu của Sánchez-Labrador (2020) và Avi Kuperschlag (2020) cho thấy ghép ngà răng tự thân vào ổ răng khôn hàm dưới sau khi nhổ giúp cải thiện chiều cao mào xương ổ và giảm độ sâu túi nha chu phía xa RCL2 3,4 . Tuy nhiên, kết quả nghiên cứu của Giulia Mazzucchi (2022) cho thấy tại tháng thứ 6 sau phẫu thuật không có sự khác biệt có ý nghĩa thống kê về sự cải thiện độ sâu túi và mức mào xương ổ giữa 2 nhóm có và không có ghép ngà tự thân 5 .…”
Section: Tóm Tắt5unclassified
See 3 more Smart Citations
“…Nghiên cứu của Sánchez-Labrador (2020) và Avi Kuperschlag (2020) cho thấy ghép ngà răng tự thân vào ổ răng khôn hàm dưới sau khi nhổ giúp cải thiện chiều cao mào xương ổ và giảm độ sâu túi nha chu phía xa RCL2 3,4 . Tuy nhiên, kết quả nghiên cứu của Giulia Mazzucchi (2022) cho thấy tại tháng thứ 6 sau phẫu thuật không có sự khác biệt có ý nghĩa thống kê về sự cải thiện độ sâu túi và mức mào xương ổ giữa 2 nhóm có và không có ghép ngà tự thân 5 .…”
Section: Tóm Tắt5unclassified
“…Kết quả này tương đồng với các nghiên cứu khác trên thế giới như của Giulia Mazzucchi (2022) và Avi Kuperschlag (2020). Trong nghiên cứu của Kuperschlag (2020), tại tháng thứ 12 sau phẫu thuật, độ sâu túi trung bình giữa 2 nhóm vẫn có sự khác biệt có ý nghĩa thống kê 3,4,5 .…”
Section: Bàn Luậnunclassified
See 2 more Smart Citations
“…Radiographic assessment also revealed that the transplanted sites had more bone gain than the control sites. The findings of this exploratory investigation show that AUTO-BG may be effective in reducing the establishment of periodontal abnormalities distal to the second lower molar after surgical extraction of the lower third molars [ 81 ].…”
Section: Clinical Applications Of Auto-bgmentioning
confidence: 99%